Reclassification of urban open green spaces for Kuala Lumpur, Malaysia - Rakhshandehroo, Mehdi (2016)
Urban open green spaces are not only at the top of the agenda of sustainability, but also play an important role in improving the livability of our town environments, But the steady increase in urban populations and expansion of urban areas has put pressure on existing urban open green spaces. As growth of built-up areas has continued to occupy areas referred to as open green spaces, it almost seems as if these spaces have been left undefined in order to accommodate their subsequent takeover. Therefore, recognizing or adopting a suitable classification of open green spaces is an important early stage in the procedure of conservation because different types of open green space may provide different, but partly overlapping sets of social, environmental, health and economic benefits to the citizens. This study involved a mixed research method to combine the strengths of both quantitative and qualitative methods by merging data. This integration is a combination of the qualitative data in the form of texts with the quantitative data in the form of numeric information (tables and charts). This methodology consists of five stages: Review of literature, Semi-structured interview (preliminary study), Qualitative questionnaire (in the 2nd round), and GIS mapping. Respondents were chosen from experts to elicit their opinions and determine the items of urban open green spaces classification. The author established a new comprehensive classification of urban open green spaces for Malaysian cities which contains 39 types, 14 categories and five classes. Any approach to the protection of open green spaces would seem to require as a first step a reasonable comprehensive understanding of the current geographical distribution of the existing green spaces within the city. The data manipulation involved was carried out in ArcGIS which thus helped to illustrate the possibilities of land parcel data for mapping open green space and of exploring visually the effects of including the further types of landuse in mapping. Therefore, the landuse data acquired from DBKL were applied as raw data to see how far the various types of comprehensive classification could be found in parcel-based data. A comparison of a current open green space map (prepared by DBKL) and a proposed map (based on suggested classification) reveals the number and area of open green spaces of KL are increased dramatically. Therefore these results are eligible to be applied and push urban policies in monitoring and preserving these many valuable spaces.